Sichuaniella deqinensis sp. nov., a new diatom species (Bacillariophyceae) from a high altitude lake in the Hengduan Mountains, SW China - Wu, Han; Zhang, Teng-Zhong; Li, Yan-Ling; Metzeltin, Ditmar; Lange-Bertalot, Horst; Patrick Kociolek, John (Phytotaxa, 2020)
A second species of the genus Sichuaniella Yan L. Li, Lange-Bertalot & Metzeltin 2013 from China is described as new to science. The new species, S. dequinensis spec. nov., is documented with light and scanning electron microscopy. This new species is distinguished from the only other species of the genus, S. lacustris, by having a higher density of more strongly radiate alveoli between broader interstriae, and a broader axial area. The new species is known only from a small lake in the Hengduan Mountains region of southwest China.